Residential Real Estate as a Potential Hedge of Capital Against Inflation - Wolski Rafal (Real Estate Management and Valuation, 2023)
There is a belief among investors that real estate is an excellent way to protect capital from depreciation due to inflation. Research does not provide a clear answer as to whether this investors’ belief is correct, but some approaches indicate that simple econometric methods are not able, especially in the short term, to clearly indicate the existence of a relationship between inflation and property prices (Fogler, 1984). The purpose of the study –was to find the relationship between residential real estate prices and inflation in the Polish economic conditions. Methodology of the study - the study used cointegration analysis with the Engle - Granger test. The research was carried out in the period from the first quarter of 2009 to the fourth quarter of 2021. The real estate hedonic indices calculated by NBP (National Bank of Poland) and the actual and forecasted inflation rates published by the GUS (Central Statistical Office) and the NBP (National Bank of Poland) were used in the research. The result - the analysis led to a negative verification of the research hypothesis, as it could not be proved that real estate prices were related to the level of inflation during the researched period. Originality/value - the study fills a gap in the Polish market regarding the analysis of the possibility of using real estate as a hedge against inflation. The research concerned only the Polish market, but this issue has not been taken up for years, also in mature economies.